UN NOUVEAU CARACTERE DISTINCTIF DES LARVES DE RHIZOTROGINI D’AFRIQUE DU NORD (Coleoptera Scrabaeidae, Melolonthinae) (Sciences & Technologie. C, Biotechnologies, 2011)
The present study is done in Constantine region; it located in semi-arid bioclimatic stage. Systematic analysis is based by the shape of a shield of anal grubs, we distinguished two forms respectful, that the Rhizotroginis European chafer (oval) (Phyllophaga sp.) And the Eurasian beetle with a V-shape. Forms that characterize Rhizotrogini North Africa are reported for the first time in Algeria. The bristles of the anal shield are placed in a parenthesis ( ) and-shaped.